1991
DOI: 10.1002/ijc.2910480318
|View full text |Cite
|
Sign up to set email alerts
|

Ras mutations in united kingdom examples of oral malignancies are infrequent

Abstract: Point mutations in codons 12, 13 or 61 of the oncogenes Ha-ras, Ki-ras or N-ras have been identified in human malignancies of many types. Using the PCR (polymerase chain reaction) technique for DNA amplification in vitro and stringent probing of the amplified DNA on dot blots with a library of specific oligonucleotides, we have screened for the presence of ras mutations in oral and para-oral malignancies and some associated lesions. The material, from UK patients, consisted of 22 oral squamous-cell carcinomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 16 publications
2
35
1
1
Order By: Relevance
“…We have confirmed and extended the observations of previous investigators (Rumsby et al, 1990;Sheng et al, 1990;Chang et al, 1991) to demonstrate that mutations in the H-ras proto-oncogene are extremely rare in the pathogenesis of H & N SCC in Caucasian patients. Extending the findings of others, we were unable to find H-ras mutations in 11 premalignant or benign lesions and 20 early stage (T1, T2) untreated SCC which were not studied by the earlier investigators.…”
Section: Discussionsupporting
confidence: 89%
“…We have confirmed and extended the observations of previous investigators (Rumsby et al, 1990;Sheng et al, 1990;Chang et al, 1991) to demonstrate that mutations in the H-ras proto-oncogene are extremely rare in the pathogenesis of H & N SCC in Caucasian patients. Extending the findings of others, we were unable to find H-ras mutations in 11 premalignant or benign lesions and 20 early stage (T1, T2) untreated SCC which were not studied by the earlier investigators.…”
Section: Discussionsupporting
confidence: 89%
“…A report from India demonstrated that 35% of oral squamous cell carcinomas contained H-ras mutations (Saranath et al, 1991). However, studies from the Western world have shown that H-ras mutations are found in fewer than 5% of head and neck cancers (Rumsby et al, 1990;Sheng et al, 1990;Chang et al, 1991;Hirano et al, 1991). In oral cancer, Kirsten ras (K-ras) has been shown to be activated by a point mutation (Spandidos et al, 1985); thus, it remains activated, but unable to hydrolyze GTP due to an amino acid change resulting from this mutation (Barbacid, 1987).…”
Section: Intracellular Messengersmentioning
confidence: 99%
“…In oral carcinomas, the frequency of Ras mutation showed great demographic variation. Ras mutation has been reported in 20-35% of the cases from India, [8][9][10] whereas lower frequencies (4%) were reported from the United Kingdom 11 and no mutation was reported from the Unites States. 12 Davies et al 13 revealed activating mutations in the B-Raf kinase gene in greater than 60% of melanomas and a broad range of other cancers.…”
mentioning
confidence: 95%